MicroEssensial Content Fe, Zn and Iod of Sipunculus nudus from Samboang Beach, Bulukumba District - Lucky Hartanti; Warsidah; Rita Kurnia Apindiati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Micro minerals are a number of minerals that the body needs to carry out its functions normally, even if only in very small amounts. The high need for minerals to improve health, especially in handling stunting in children during the growth and development period, encourages the search for food sources that are cheap and easy to consume. Sipunculus nudus is a marine animal that lives immersed in sand where the waters are relatively fertile, and is often found in the East of South Sulawesi region. The aim of this research is to determine the micro mineral content of iron (Fe), zinc (Zn) and iodine (I) in the meat of S. nudus in Samboang waters. Fe and Zn were determined using an atomic absorption spectrophotometer, while iodine was determined using an HPLC instrument. The results showed that the S. nudus sample contained Fe and Zn of 221.43 ppm and 21 ppm respectively, and the mineral Iodine (I) was 14.11 ppm.